2016
DOI: 10.14478/ace.2016.1093
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Cellular Protective Effects against Oxidative Stress of Calendula officinalis Flowers Extracts in Human Skin Cells

Abstract: In this study, we investigated the total phenolic and flavonoid contents, antioxidant activity and cellular protective effects against oxidative stress on human skin cells in 50% ethanol extract and its fractions of Calendula officinalis (C. officinalis) flowers. We measured the antioxidant effects of 50% ethanol extract and its fractions of C. officinalis flowers on the free radical scavenging activity (FSC50), the reactive oxygen species (ROS) scavenging activities (OSC50) and the inhibition of intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In our previous study, we reported that EFC contains flavonoids and polyphenols . To further identify the bioactive compounds in EFC, HPLC and LC‐MS/MS were used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we reported that EFC contains flavonoids and polyphenols . To further identify the bioactive compounds in EFC, HPLC and LC‐MS/MS were used.…”
Section: Resultsmentioning
confidence: 99%
“…The 50% ethanol extract was fractionated with ethyl acetate three times and concentrated with a rotary evaporator for 6 h to obtain an ethyl acetate fraction powder. Then, the dried samples were stored at—80°C in the refrigerator (Cosmetic R&D Center, Seoul National University of Science and Technology, Seoul, Korea) until use .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, UV irradiation to the skin activates collagenases within the skin, which degrades collagen that contributes to the elasticity of the skin, and accelerates the dryness and aging of the skin (Imokawa et al, 2015). As these studies show, excessive oxidative stress generated by continuous exposure to UV light cuts the chains of collagen, elastin and hyaluronic acid and accelerates the creation of melanin, which reduces skin elasticity and causes skin aging along with wrinkles and pigmentation (Ha et al, 2015;Xuan et al, 2016). The increasing activity of keratinocytes caused by UVB irradiation induces the creation of cytokines, and activates fibroblasts, generating cytokines and the expression of MMP -1 proteins (Kim et al, 2018).…”
Section: Assessment Of In-vivo Anti-photoaging Effectmentioning
confidence: 99%
“…Calendula possesses many phytochemicals and pharmacological activities to be considered an excellent source of new drugs 2 . Many of these bioactive substances find application as antioxidants in cosmetics 3 . Extracts from calendula protect cells against UV radiation, stimulate skin cell regeneration, and improve skin elasticity 4 .…”
Section: Introductionmentioning
confidence: 99%